Supplementation of Mangosteen Pericarp Meal and Vitamin E on Egg Quality and Blood Profile of Laying Hens - R. K. Rusli; K. G. Wiryawan; T. Toharmat; . Jakaria; R. Mutia (Media Peternakan, 2015)
This research aimed to study the supplementation effects of mangosteen pericarp meal (MPM) and vitamin E (VE) in the diets on the egg quality and blood profile of laying hens. This research used 160 laying hens of Lohman strains 24 weeks of age. The observation was conducted for 11 weeks. A completely randomized design with four treatments and four replications (10 birds each) was used in this experiment. The treatments consisted of R0 (control diet), R1 (R0 + 1 g MPM/kg ration), R2 (R0 + 2 g MPM/kg ration) and R3 (R0 + 200 mg VE/kg ration). Variables measured were egg quality, yolk cholesterol, and blood profiles. The data were analyzed by using analysis of variance (ANOVA) and any significant difference between the treatment means were further tested by Duncan’s Multiple Range Test. The results showed that supplementation of 1 g MPM/kg ration in the diet significantly (P<0.05) decreased blood triglycerides compared with the control, laying hens fed with diet suplemented with of 2 g MPM/kg ration, and laying hens with diet suplemented with 200 mg VE/kg  ration. Supplementation of MPM and VE did not affect (P>0.05) egg quality (except shell thickness), blood cholesterol, and HDL, respectively. In conclusion, supplementation of 1 g MPM/kg in the diet of laying hens could decrease blood triglycerides.Key words: blood profile, laying hens, mangosteen pericarp meal, egg quality, vitamin E